Microbial landscape of cooked meat products: evaluating quality and safety in vacuum-packaged sausages using culture-dependent and culture-independent methods over 1 year in a sustainable food chain - Lemos Junior, Wilson José Fernandes; Marques Costa, Lucas; Alberto Guerra, Carlos; Sales de Oliveira, Vanessa; Gava Barreto, Angela; Alves de Oliveira, Fabiano; Paula, Breno Pereira de; Esmerino, Erick Almeida; Corich, Viviana; Giacomini, Alessio; Guerra, André Fioravante (Frontiers in Microbiology, 2024)
Over the last decades, advancements in process safety and quality methods have been significant, yet new challenges continue to emerge in the sustainable food supply chain.This study aims to investigate some physicochemical and microbiological parameters impacting meat products, particularly cooked sausages, within a sustainable supply chain, focusing on quality and spoilage populations, and syneresis formation under vacuum conditions. A comprehensive analysis was conducted on 355 samples collected over four seasons, using high-throughput sequencing (16S/ITS), microbiological and physicochemical (pH and water activity (aw)) assessments. The microbial growth predictor MicroLab_ShelfLife was employed, and Multiple Factor Analysis (MFA) and Agglomerative Hierarchical Clustering (AHC) were utilized to understand how these variables influence the microbiome resilience of these products. Lactic and acetic acids were correlated with the sausages microbiome and covering liquid coating using metagenomic analyses. The study highlighted that 52% of the evaluated meat industries in Southeastern Brazil are implementing effective protocols for sustainable chain production. Results indicated that the durability of vacuum-packaged cooked sausages was primarily influenced by storage temperature (RV coefficient of 0.906), initial microbial load (0.755), and aw (0.624). Average microbial counts were 4.30 log cfu/g (initial), 4.61 (7°C/4 days), 4.90 (7°C/8 days), 6.06 (36°C/4 days), and 6.79 (36°C/8 days). Seasonal durability analysis revealed winter had the highest average durability of 45.58 days, while summer had the lowest at 26.33 days. Yeast populations, including Trichosporon sp. and Candida sp., were identified as key genera influencing spoilage dynamics. Additionally, Bacillus species emerged as dominant spoilage microorganisms, highlighting the need for new critical controls. This study demonstrates the impact of metagenomic approaches, including ITS and 16S amplicon sequencing, in revealing microbial community dynamics, storage temperature and aw essential for developing targeted interventions to enhance food safety and quality sustainably.